2017
DOI: 10.1021/acsami.7b08770
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of SnS with Na-Doping

Abstract: Tin sulfide (SnS), a low-cost compound from the IV-VI semiconductors, has attracted particular attention due to its great potential for large-scale thermoelectric applications. However, pristine SnS shows a low carrier concentration, which leads to a low thermoelectric performance. In this work, sodium is utilized to substitute Sn to increase the hole concentration and consequently improve the thermoelectric power factor. The resultant Hall carrier concentration up to ∼10 cm is the highest concentration report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 69 publications
6
89
1
Order By: Relevance
“…[1][2][3] In general, TE materials that contain inexpensive earth-abundant and nontoxic elements are the most interesting applications. [32,33] The recent study using polycrystalline SnS samples was rather disappointing in its outcome as it resulted in a relatively low zT value of 0.65 at 850 K, [34] suffering chiefly from the low power factors of the polycrystalline samples. [26] The analogous crystal structure of SnS to SnSe has suggested that potentially it should also have ultralow lattice thermal conductivity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] In general, TE materials that contain inexpensive earth-abundant and nontoxic elements are the most interesting applications. [32,33] The recent study using polycrystalline SnS samples was rather disappointing in its outcome as it resulted in a relatively low zT value of 0.65 at 850 K, [34] suffering chiefly from the low power factors of the polycrystalline samples. [26] The analogous crystal structure of SnS to SnSe has suggested that potentially it should also have ultralow lattice thermal conductivity.…”
mentioning
confidence: 99%
“…The DOS effective mass obtained from fitting slightly increased with temperature for the undoped sample. Note, however, that in comparison to the effect of Na doping in SnSe, [27] the doping efficiency of Na [34] and Ag [38] are shown for comparison. Figure 3 displays the temperature-dependent electronic properties of undoped and Na-doped SnS single crystals along the b-axis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is due to its extremely low thermal conductivity of 0.29 W m −1 K −1 and large Seebeck coefficient of 403 µV K −1 . A highest thermoelectric zT of 0.65 is reported in polycrystalline SnS by doping with Na . Similarly, a very low lattice thermal conductivity of SnSe makes a good zT of 1.1 at 773 K .…”
Section: Introduction To Thermoelectricsmentioning
confidence: 99%